2009
DOI: 10.1016/j.cellbi.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Antisense down regulation of connexin31.1 reduces apoptosis and increases thickness of human and animal corneal epithelia

Abstract: The roles of the gap junction protein connexin31.1 (Cx31.1) are poorly understood, especially as the protein appears to form non-functional channels. Cx31.1 specific antisense oligodeoxynucleotides (ODNs) were designed to evaluate its roles in a corneal epithelium model. Expression of Cx31.1 in corneal epithelium extends from the suprabasal layers of polyhedral wing cells through to the flat squamous cells of superficial layers which are shed into the tear film. Deoxyribozymes (Dzs) were tested for cleavage ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…In the current experiment, it was identified that Cx31.1 expression levels were significantly higher at the mRNA and protein levels in the chemically burned and infected corneas. These findings support the results of Chang et al (6) , as following chemical burns and infection, apoptosis is triggered both in corneal epithelial cells and corneal keratocytes (40). The present results, together with those of Chang et al further indicate that antisense Cx31.1 is likely to be a promising candidate for the treatment of corneal wounds.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current experiment, it was identified that Cx31.1 expression levels were significantly higher at the mRNA and protein levels in the chemically burned and infected corneas. These findings support the results of Chang et al (6) , as following chemical burns and infection, apoptosis is triggered both in corneal epithelial cells and corneal keratocytes (40). The present results, together with those of Chang et al further indicate that antisense Cx31.1 is likely to be a promising candidate for the treatment of corneal wounds.…”
Section: Discussionsupporting
confidence: 92%
“…Following antisense Cx31.1 treatment in rat and human corneal organotypic culture models, not only was there evidence for Cx31.1 knockdown, but also the cornea epithelium appeared significantly thicker within just 24 h and a marked reduction in epithelial apoptotic cell numbers was observed. The results indicated that Cx31.1 may play a role in triggering apoptosis, leading to cell sloughing into the tear film (6). In the current experiment, it was identified that Cx31.1 expression levels were significantly higher at the mRNA and protein levels in the chemically burned and infected corneas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of Cx31.1 antisense oligonucleotides in ex vivo rodent and human corneal models results in decreased epithelial cell apoptosis and increases in corneal thickness. The mechanism of action is likely linked to roles for Cx31.1 in the reduction in superficial cell death and shedding [101]. Additional research investigating the mechanism is required to fully elucidate the clinical potential of targeting Cx31.1 in the cornea.…”
Section: Lessons Learned From Wound Healingmentioning
confidence: 99%
“…Connexin 31.1 (Cx31.1) protein is predominantly expressed in the corneal epithelium and the skin epidermis (Chang et al, 2009;Goliger and Paul, 1994;Hennemann et al, 1992). It leads to formation of nonfunctional gap junction channels between cells and is therefore associated with cell apoptosis.…”
Section: Introductionmentioning
confidence: 95%